Pemilihan Guru Terbaik Berbasiskan Web menggunakan Metode Simple Additive Weighting - Sumardiono; Zahra Qotrun Nida (Ikatan Ahli Informatika Indonesia, 2024)
The complete information system is technology that is based on the thoughts of people who have interests; the aim is to assist in the activities of these people, especially in an organization such as a school, one of which is selecting the best teachers. We still consider the selection of the best teacher in a school to be subjective, as it involves the appointment of a leader or principal, either without or with the support of objective data. The research is a case study at one of the vocational schools in Bekasi City. This research was carried out using a quantitative approach by developing a web-based system using the Simple Additive Weighting (SAW) method. This SAW method explains values from normalization to preference and ranking, making it easier to determine and select the object in question, namely the best teacher. The results of this research were measured by a usability value of 89%, a reliability value of 88%, an efficiency value of 91%, and a functionality value of 91%. By looking at several system testing factors above, it can be concluded that web-based best teacher selection is ready to be used at the vocational school.